Formulation, development and evaluation of patient friendly dosage forms of metformin, Part-II: Oral soft gel - Mohapatra, Ashutosh; Parikh, Rajesh K; Gohel, Mukesh C (Asian Journal of Pharmaceutics (AJP), 2014)
Dionvenience of administration and patient compliance are gaining significant importance in the design of dosage forms. Metformin hydrochloride is an orally administered antihyperglycemic agent, used in the management of non-insulin-dependant (type-2) diabetes mellitus. Difficulty in swallowing (dysphagia) is common among all age groups, especially in elderly and pediatrics. Unfortunately, a high percentage of patients suffering from type-2 diabetes are elderly people showing dysphagia. Persons suffering from dysphagia may get choked when they consume liquid formulation, thus to alleviate such problem liquid formulation of high viscosity was prepared. Formulation of oral soft gel batches of metformin was carried out using hydrophilic polymer gellan gum at concentrations ranging from 0.2-0.4% w/v and sodium citrate at two different concentrations (0.3% and 0.5%). The prepared batches were evaluated for appearance, viscosity, pH, drug content, syneresis, in vitro drug release, and taste masking. The batch with 0.4% w/v gellan gum and 0.5% sodium citrate not only showed 85% drug release at 15 min, but all the desired organoleptic properties. The taste masking was carried out using nonnutritive sugar and flavors.The optimized batch showed substantial stability when subjected to short term stability study (0-8Â°C and Room temperature). The problem of dose measurement by patients was outweighed as oral medicated gels are to be packed in unit dose container.